Preparation and Characterization of Barium Hexaferrite Thin Films - Singh, Jatinder (My University, 2017)
In recent years, BaM (BaFe12O19) are the most interesting topic in the research because of its application in magnetic recording media, microwave devices and millimeter wave devices. It shows high resistivity, high chemical stability andgood magnetic properties. Recently, the focus of the researcher has been laid to the development of thin and thick films, owing to its versatile above mentioned properties. In the present work, BaFe12O19 thin films are prepared by magnetron sputtering technique. The main focus was to understand the effect of deposition time and annealing temperature on the structural and magnetic properties of BaFe12O19 thin films.
Keywords: hexaferrite; thin film; magnetic properties